MUSIC THERAPY: INNOVATIVE STRATEGIES AND SOLUTIONS FOR A MULTIDISCIPLINARY APPROACH TO DESIGN SPACES WITH HIGH ACOUSTIC PERFORMANCES - Diletta Romagnolo; Angelo Bertolazzi; Giorgio Croatto; Eleonora Strada; Umberto Turrini (Valori e Valutazioni)
The paper presents the first research results concerning the identification of innovative building design solutions for the performance of Music Therapy, by the use of both modular nZEB (Nearly Zero Energy Building) technology and a specific variable absorption acoustic design. To date, both in Italy and abroad, spaces for Music Therapy are configured as inadequate environments, since they lack specific acoustic properties. The final effectiveness of the therapeutic treatment, carried out on fragile subjects, is undermined by the fact that such spaces are mainly improvised or not specifically designed for this activity. To respond to these critical issues, various modular building solutions with specific functions (therapeutic and administrative) have been evaluated. On these solutions, especially on the therapy rooms, acoustic assessments have been carried out using variable absorption acoustic design specifically tailored to the type, position and movement of corrective sound furniture and to the various sound sources in the environment. These assessments have proven to be of fundamental importance to ensure an effective dialogue between the different needs of patients and professionals.